Abyssal macrofaunal community structure in the polymetallic nodule exploration area at the easternmost region of the Clarion-Clipperton Fracture Zone, Pacific Ocean. (July 2020) - Chuar, Cheah Hoay; Tong, Samantha Jia Wen; Chim, Chee Kong; Wong, Helen Pei San; Tan, Koh Siang
Abstract: Benthic communities in the deep sea are often characterized by high diversity, contrary to the once held view of the deep sea as an environment desolate of life. Heightened commercial interest in polymetallic nodule mining in the abyssal Clarion-Clipperton Fracture Zone (CCFZ) have seen a number of exploratory expeditions to the area. However, macrobenthic community structure is still poorly characterized across this extensive habitat. This study aims to fill in the knowledge gap at the easternmost region of the CCFZ where sea surface productivity is known to be relatively higher compared to other areas. A total of 5199 metazoan individuals (macrofauna sensu lato, > 250 μm) were collected from the top 10 cm sediment layer in 12 box core samples obtained from 12 stations assigned randomly within a 30 by 30 km survey stratum in the Ocean Mineral Singapore (OMS) contract area. Mean macrofaunal abundance (635 ± 54 ind.m −2, n = 12; macrofauna sensu stricto, > 300 μm) in the OMS survey area was higher than all but one locality west of the OMS area in the CCFZ. Total metazoan diversity (Hʹ) was positively and significantly correlated with volume and surface area of nodules, whilst macrofaunal abundance was significantly but negatively correlated with sediment shear strength. Not unexpectedly, the Nematoda was the most abundant metazoan group (29.3%). Other major infaunal groups comprised the Copepoda (21.2%), Polychaeta (17%), Tanaidacea (8.9%), Ostracoda (5.9%), Isopoda (4.4%) and Bivalvia (2.8%). We identified four of these groups (i.e., Polychaeta, Copepoda, Isopoda and Tanaidacea) to family level. Polychaetes exhibited the highest family richness (42 families) while the copepods (15 families), tanaids (10 families) and isopods (8 families) recorded high to moderate richness. Multivariate analyses suggested that whilst all major infaunal groups occurred in the 12 stations, the family composition of these groups (polychaetes, isopods and tanaids) differed between the stations, showing that community structure was not the same across all the stations. Small differences in sediment shear strength, nodule volume and surface cover might contribute to dissimilarities in the community structure of isopods and tanaids. The 900 km 2 OMS survey area located at the easternmost region of CCFZ is characterized by a high abundance of abyssal macrofauna that is spatially variable taxonomically even when examined at family level. Highlights: First quantitative insight into macrofaunal community structure at easternmost CCFZ. Macrofaunal abundance was higher than most other previously studied locations. Total metazoan diversity was positively correlated with nodule density and size. Macrofaunal communities were similar at phylum and class levels across all 12 stations, but not at family level for polychaetes, isopods and tanaidaceans.